The impact of summerizing & self-questioning on the improvement of iranian efl learners' reading Comprehension ability - mojhgan rashtchi (Matn/Pizhūhī-i Adabī, 2005)
The ability to read is acknowledged to be the most stable and durable of the foreign language modalities. Learners may use productive skills, yet still be able to comprehend texts with some degree of proficiency. Reading, whether in second or foreign language context, involves the reader, the text, and the interaction between the reader and text (Bernhardt, 1991 ). The present study was aimed at exploring whether summarizing the text and making comprehension questions had any statistically significant impact on the improvement of Iranian EFL learners' reading comprehension ability or not and if they had, which one was more effective - summarizing or self-questioning. In order to arrive at a logical answer to the aforementioned problems 127 university students were chosen from a pool of 160 students majoring in English Language Translation in Islamic Azad University at Garmsar. Three homogenized groups of students, who were taking a Reading course, participated as the subjects in one control and two experimental groups. While the subjects in the experimental group of self-questioning were required to read the material and generate questions and the experimental group of summarizing were supposed to read the texts and write a summary, the subjects in the control group were asked to read the materials and use some other reading strategies. At the end of the term, a newly developed reliable test was administered to determine the influence of the treatments on the groups. The results signified that self-questioning did not have much impact on improvement of students' reading comprehension ability, while summarizing affected their reading comprehension ability. Therefore, it was concluded that using summarizing in teaching reading could have positive effects on reading comprehension ability of EFL learners.